Intratumoral T‐cell receptor repertoire is predictive of interim PET scan results in patients with diffuse large B‐cell lymphoma treated with rituximab/cyclophosphamide/doxorubicin/prednisolone/vincristine (R‐CHOP) chemoimmunotherapy. Issue 11 (27th October 2021) - Shanavas, Mohamed; Law, Soi‐Cheng; Hertzberg, Mark; Hicks, Rodney J; Seymour, John F; Li, Zhixiu; Merida de Long, Lilia; Nath, Karthik; Sabdia, Muhammed B; Gunawardana, Jay; Gandhi, Maher K; Keane, Colm
Abstract: Objectives: A diverse intratumoral T‐cell receptor (TCR) repertoire is associated with improved survival in diffuse large B‐cell lymphoma (DLBCL) treated with rituximab/cyclophosphamide/doxorubicin/prednisolone/vincristine (R‐CHOP) chemoimmunotherapy. We explored the impact of intratumoral TCR repertoire on interim PET (iPET) done after four cycles of R‐CHOP, the relationships between intratumoral and circulating repertoire, and the phenotypes of expanded clonotypes. Methods: We sequenced the third complementarity‐determining region of TCRβ in tumor samples, blood at pre‐therapy and after four cycles of R‐CHOP in 35 patients enrolled in ALLGNHL21 trial in high‐risk DLBCL. We correlated the TCR diversity metrics with iPET status, gene expression profiles and HLA‐class I genotypes. We then sequenced the FACS‐sorted peripheral blood T cells in six patients, and pentamer‐sorted EBV‐specific CD8 + T cells in one patient from this cohort. Results: Compared with iPET − patients, the intratumoral TCR repertoire in iPET + patients was characterised by higher cumulative frequency of abundant clonotypes and higher productive clonality. There was a variable overlap between circulating and intratumoral repertoires, with the dominant intratumoral clonotypes more likely to be detected in the blood. The majority of shared clonotypes were CD8 + PD‐1 HI T cells, and CD8 + T cells had the largest clonal expansions in tumor and blood. In a patient with EBV + DLBCL, EBV‐specific intratumoral clonotypes were trackable in the blood. Conclusion: This study demonstrates that clonally expanded intratumoral TCR repertoires are associated with iPET + and that the blood can be used to track tumor‐associated antigen‐specific clonotypes. These findings assist the rationale design and therapeutic monitoring of immunotherapeutic strategies in DLBCL. Abstract : In a cohort of high‐risk diffuse large B‐cell lymphoma patients enrolled in phase 2 clinical trial, clonally expanded intratumoral TCR repertoires were associated with a positive interim PET scans. Abundant intratumoral clonotypes were identified in peripheral blood at baseline and during chemoimmunotherapy.